Incidence of cervical cytological abnormalities following a negative smear result in an opportunistic screening scenario: A cohort study. (November 2019) - Pinho-França, José de Ribamar; Costa Chein, Maria Bethânia da; Thuler, Luiz Claudio Santos
Abstract: Objectives: To analyse the incidence of atypical cells and their risk factors in an opportunistic screening context. Study design: This cohort study with passive follow-up is based on analysis of 86, 609 women living in Maranhão State - Brazil, who had a negative cervical cytological test recorded in the Cervical Cancer Information System (SISCOLO) in 2007 and who had at least 1 follow-up test up to 31 December 2012. The cumulative incidence (CI) and incidence rate (IR) of low grade squamous intraepithelial lesion (LSIL) and high-grade squamous intraepithelial lesions and cancer (HSIL+) were calculated. A Cox regression model was used to identify independent factors associated with the risk of presenting atypical cells. Results: At 60 months follow-up the CI of LSIL reached 10.7 per 1000 and that of HSIL + was 3.9 per 1000. LSIL and HSIL + IRs were 334.7 and 120.3 per 100, 000 person-years (PYs), respectively. LSIL and HSIL + occurred in 65.0% and 57.3% of women <3 years after the study entry, respectively. The risk of presenting HSIL + increased when a previous cervical cytological test had not been performed, with advancing age and when the Municipal Human Development Index (MHDI) decreased. Conclusion: This study highlights a significant tendency towards increased IR and risk of presenting HSIL + as MHDI decreased.